5-({3-[(5-Amino-1,3,4-thiadiazol-2-yl)sulfanylmethyl]benzyl}sulfanyl)-1,3,4-thiadiazol-2-amine - Sung Kwon Kang (Acta Crystallographica Section E, 2012)
In the title compound, C12H12N6S4, the two terminal thiadiazole rings are twisted with respect to the central benzene ring, making dihedral angles of 54.28 (4) and 76.56 (3)°. The dihedral angle between the two thiadiazole rings is 27.77 (4)°. Intermolecular N—H...N hydrogen bonds stabilize the crystal packing, linking the molecules into a tape along the b axis.